Optogenetics in plants. Issue 6 (28th November 2020) - Christie, John M.; Zurbriggen, Matias D.
Summary: The last two decades have witnessed the emergence of optogenetics; a field that has given researchers the ability to use light to control biological processes at high spatiotemporal and quantitative resolutions, in a reversible manner with minimal side‐effects. Optogenetics has revolutionized the neurosciences, increased our understanding of cellular signalling and metabolic networks and resulted in variety of applications in biotechnology and biomedicine. However, implementing optogenetics in plants has been less straightforward, given their dependency on light for their life cycle. Here, we highlight some of the widely used technologies in microorganisms and animal systems derived from plant photoreceptor proteins and discuss strategies recently implemented to overcome the challenges for using optogenetics in plants.